Assessment of labor progression by intrapartum ultrasonography among term nulliparous women. Issue 1 (29th July 2019) - Mohan, Anubhuti; Mittal, Pratima; Bharti, Rekha; Grover, Shabnam Bhandari; Suri, Jyotsana; Mohan, Usha
Abstract: Objective: To assess cervical dilation, fetal head station, and fetal head position by intrapartum ultrasonography and to compare the approach with digital vaginal examination (DVE). Methods: An observational study conducted from October 2015 to January 2017 among term nulliparous women in active labor at a tertiary hospital in Delhi, India. Cervical dilation, head station, and head position were assessed by DVE, followed by ultrasonography within 10 minutes. The women's preference was also evaluated. Results: Overall, 458 observations were obtained for 215 women. Cervical dilation measured by DVE was strongly correlated with ultrasonography findings (intraclass correlation coefficient, 0.945; 95% confidence interval, 0.932–0.956; κ=0.837; P <0.001). Data for fetal head station and head position showed a fair correlation (κ=0.353 and κ=0.554, respectively; both P <0.001). The majority of women (186/215, 87%) reported a preference for ultrasonography over DVE for assessment of labor progression in a future pregnancy. Conclusion: Intrapartum ultrasonography was preferred as an objective assessment tool for labor progression among term nulliparous women and therefore should be practiced in all labor rooms. Further studies on interobserver variation are recommended to establish the reproducibility of intrapartum assessment by ultrasonography. Abstract : Intrapartum ultrasonography was found to be an objective and noninvasive method to assess progress of labor. Women preferred ultrasonography to digital vaginal examination.